A stranger in a strange land: experiences of adjustment among international postgraduate students in Malaysia - Dahalan, Dzuhailmi; Abdullah, Abdul Lateef; Abdullah, Haslinda; Ahrari, Seyedali; Abdullah Sahimi, Nur Aishah Hamizah; Olutokunbo, Adekalu Samuel; Turiman, Suandi (Western Australian Institute for Educational Research, 2019)
Despite the ongoing globalisation of higher education, few studies have attempted to understand international students' adjustment experiences in non-Western institutions of higher learning. This study employed in depth, semi-structured interviews to explore the adjustment experiences of 10 international postgraduate students in Malaysia. Three themes and twelve sub-themes emerged from the interviews, including academic adjustment (academic experiences with English language, different teaching and learning approaches, experiences with student support services, and academic support), psychological adjustment (safety and peacefulness, loneliness, anxiety and stress, and homesickness), and sociocultural adjustment (perceived discrimination, language and communication challenges, personal friendships with local students, and culture shock). The theoretical and practical implications are outlined in regard to international students' expectations and experiences of living and studying in Malaysia.